Constraining hadronization mechanisms with Λc+/D0 production ratios in Pb–Pb collisions at sNN=5.02 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Adolfsson, J.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akbar, Z.; et al. (Elsevier, 2023)
The production of prompt + c baryons at midrapidity (|y| < 0.5) was measured in central (0–10%) and mid-central (30–50%) Pb–Pb collisions at the center-of-mass energy per nucleon–nucleon pair √sNN = 5.02 TeV with the ALICE detector. The results are more precise, more differential in centrality, and reach much lower transverse momentum (pT = 1 GeV/c) with respect to previous measurements performed by the ALICE, STAR, and CMS Collaborations in nucleus–nucleus collisions, allowing for an extrapolation down to pT = 0. The pT-differential + c /D0 ratio is enhanced with respect to the pp measurement for 4 < pT < 8 GeV/c by 3.7 standard deviations (σ), while the pT-integrated ratios are compatible within 1σ. The observed trend is similar to that observed in the strange sector for the /K0 S ratio. Model calculations including coalescence or statistical hadronization for charm-hadron formation are compared with the data.
Keywords: Physics; Hadronization; Nuclear physics; Baryon; Particle physics; Hadron; Extrapolation; Coalescence (physics); Statistics; https://purl.org/pe-repo/ocde/ford#1.03.04